Faktor-faktor yang Berhubungan Dengan Kemitraan Bidan dengan Dukun Bayi dalam Melakukan Pertolongan Persalinan di Wilayah Kerja Puskesmas Cirinten - Yaneu Nuraineu; Ayi Tansah Rohaeti (Jurnal Obstretika Scientia, 2022)
The Cirinten Public Health Center is one of the health centers in Lebak Regency, from initial data obtained from the Health Office, it was known at this health center in 2012 that the birth rate by health workers was still low at 58.93%, which was the second lowest coverage of other health centers that in Lebak Regency. The socialization of the partnership between midwives and traditional birth attendants in Lebak Regency has been carried out since 2007 in conjunction with the Delivery Planning and Complications Prevention Program (P4K). The purpose of this study was to find out what factors were related to the partnership between traditional birth attendants and midwives in providing delivery assistance in the work area of the Cirinten Public Health Center, Lebak Regency in 2012. This type of research was an analytical survey using a cross selection design approach, to describe the partnership between traditional birth attendants and traditional birth attendants. midwives and factors related to the partnership between traditional birth attendants and midwives in providing delivery assistance in the work area of the Cirinten Health Center. Respondents were 61 traditional healers who were in the work area of the Cirinten Health Center. The results of the study illustrate that the implementation of the partnership at the Cirinten Health Center has not met expectations. Most of the traditional birth attendants in the work area of the Cirinten Public Health Center, Lebak Regency are 40 years old (93.4%), have never received training with traditional birth attendants (55.7%), have a positive attitude about partnerships (70.5%) and have partnerships with traditional birth attendants. midwife in providing delivery assistance (72.1%). There is a relationship between training (p = 0.021) and attitudes (p = 0.001) with the partnership between traditional birth attendants and midwives in providing delivery assistance in the work area of the Cirinten Health Center, Lebak Regency in 2012. There is no relationship between the age of the traditional birth attendant and the partnership between the traditional birth attendant and the midwife in perform delivery assistance with a value of p = 0.308.